THz Scattering and Tunable Plasmonic Resonances from Graphene-Coated Gold Nanowires - Faroq Razzaz; M. N. Akram; M. Z. Yaqoob (International Journal of Antennas and Propagation)
The radiative response of antenna structures highly depends upon the extinction efficiency of the structures and the major parameter for the optimization of nanoantenna designs. To optimize the radiative response of the plasmonic antenna design, i.e., the oblique scattering of the THz radiation form, graphene-coated gold (Au) nanowires have been studied. The present work provides a universal solution for the graphene-coated cylindrical geometries. The optical conductivity of graphene has been modeled by the use of Kubo formalism, while the analytical modeling of the gold (Au) is done by employing Drude’s model. The Jacobi–Anger expansion method has been adopted for the transformation of electromagnetic fields in terms of series of cylindrical waves and has been modeled in terms of cylindrical vector wave functions (CVWFs). The analytical formulation has been presented for both polarizations, i.e., parallel polarization (TM) and perpendicular polarization (TE). The unknown scattering coefficients have been calculated by applying impedance boundary conditions at graphene-gold nanowire interface. The analytical and numerical results have been computed for extinction efficiency Qext under parallel and perpendicular polarization states. The Qext under different parameters of graphene, diameter of metallic nanowire (R) and angle of incidence θi, has been computed. It is reported that the graphene-coated Au nanorod supports the localized surface plasmon resonance (LSPR) under perpendicular polarization at a high THz frequency range. The surface plasmon resonance can be actively controlled under suitable parameters, i.e., graphene parameters, core size, and angle of incidence. The numerical results reveal that the radiative response of the plasmonic structures can be tuned actively from THz to Far-IR frequency range under appropriate parameters. The provided results have potential applications in subwavelength devices and plasmonic antenna designs.